Women and Culinary: From Domestic to Public Kitchen - Liliek Budiastuti Wiratmo (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
The widespread ulinary programs in television has brought domestic activity into the public sphere. When start to be shown at public domain, such as shops, hotel, restaurant and even televi- sion, the activity which was originally conceived as women’s work in the house begin to be possesed by men. The emergence of men as host chef in the culinary program confirms the dominance of men in public spaces, which is packaged as a television performance that shown how men as it is but also show their ability in food processing. This is different when we enter the era which women host no longer placed as a mother who cooked for the family, but as chef and host with ‘catchy’ packaging. This paper highlights how the culinary program seen from the sex based job classification, how male dominance in the culinary program on television, as well as how women compete to fight for culinary stage on screen.